2001
DOI: 10.1007/s004410000302
|View full text |Cite
|
Sign up to set email alerts
|

Topology of the signal transduction of the G protein-coupled somatostatin receptor sst 2 in human glioma cells

Abstract: By a dual approach, using electron microscopy and biochemical techniques, we investigated the topology of the somatostatin receptor sst2 with its inhibitory G protein Gialpha after ligand-induced stimulation and internalization in human glioma cells. On intact cells, the sst2 was labeled at 8 degrees C by an antibody directed to its extracellular sequence followed by a 15-nm gold-labeled secondary antibody. In the presence of the ligand, internalization was induced by exposure to 37 degrees C for 5-10 min. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
(32 reference statements)
2
19
0
Order By: Relevance
“…A number of paradigms have recently emerged (Fig. 2), and an example is given of each: (a) the receptor moves into lipid rafts/caveolae upon agonist binding and, like the somatostatin receptor sst2, is internalised via this pathway (Krisch et al 1998, Mentlein et al 2001; (b) the receptor moves into lipid rafts after agonist binding in order to activate specific signalling events, but eventually moves out to be internalised via CCPs, as in the case of the AT1 receptor (Ishizaka et al 1998, Wyse et al 2003; (c) the receptor is mainly in lipid rafts and enters cells via this pathway by default, such as the ET A receptor (Chun et al 1994, Okamoto et al 2000; and (d) the receptor is in lipid rafts but leaves after agonist binding to be internalised via CCPs, such as the 2 -AR (Schwencke et al 1999, Rybin et al 2000.…”
Section: When Do Gpcrs Go To Lipid Rafts/caveolae? (Role Of Lipid Rafmentioning
confidence: 99%
“…A number of paradigms have recently emerged (Fig. 2), and an example is given of each: (a) the receptor moves into lipid rafts/caveolae upon agonist binding and, like the somatostatin receptor sst2, is internalised via this pathway (Krisch et al 1998, Mentlein et al 2001; (b) the receptor moves into lipid rafts after agonist binding in order to activate specific signalling events, but eventually moves out to be internalised via CCPs, as in the case of the AT1 receptor (Ishizaka et al 1998, Wyse et al 2003; (c) the receptor is mainly in lipid rafts and enters cells via this pathway by default, such as the ET A receptor (Chun et al 1994, Okamoto et al 2000; and (d) the receptor is in lipid rafts but leaves after agonist binding to be internalised via CCPs, such as the 2 -AR (Schwencke et al 1999, Rybin et al 2000.…”
Section: When Do Gpcrs Go To Lipid Rafts/caveolae? (Role Of Lipid Rafmentioning
confidence: 99%
“…These observations have raised questions about the relationship between the compartmentalization of receptor-caveolae/lipid rafts and the mode of endocytic entry. In this regard, the following paradigms have been demonstrated for different 7TM receptors: (1) receptors cluster to the caveolae/lipid rafts, but after agonist binding, the internalization is clathrin-dependent (Rybin et al 2000), (2) receptors translocate to the caveolae/lipid rafts after agonist binding and then internalize via either caveolae/ lipid-rafts (Krisch et al 1998;Mentlein et al 2001) or a clathrin-dependent pathway (Wyse et al 2003), and (3) receptors mainly reside in the caveolae/lipid rafts and enter this pathway by default (Okamoto et al 2000).…”
Section: Introductionmentioning
confidence: 97%
“…Subcellular fractionation of these low-density domains and immunological studies with caveolin have identified a diverse range of GPCRs present in caveolae, including endothelin receptors [114], ß-adrenoceptors [115], oxytocin receptors [116] and somatostatin receptors [117]. For some receptors, such as angiotensin receptors [118], m 2 muscarinic receptors [119] and B 2 bradykinin receptors [120], their presence in caveolae is increased following agonist treatment.…”
Section: Receptors In Caveolaementioning
confidence: 99%